Applications of Systems Thinking and Soft Operations Research in Managing Complexity From Problem Framing to Problem Solving - Masys, Anthony J. (Advanced Sciences and Technologies for Security Applications, 2016)
This book captures current trends and developments in the field of systems thinking and soft operations research which can be applied to solve today's problems of dynamic complexity and interdependency. Such 'wicked problems' and messes are seemingly intractable problems characterized as value-laden, ambiguous, and unstable, that resist being tamed by classical problem solving. Actions and interventions associated with this complex problem space can have highly unpredictable and unintended consequences. Examples of such complex problems include health care reform, global climate change, transnational serious and organized crime, terrorism, homeland security, human security, disaster management, and humanitarian aid. Moving towards the development of solutions to these complex problem spaces depends on the lens we use to examine them and how we frame the problem. It will be shown that systems thinking and soft operations research has had great success in contributing to the management of complexity. .